Measuring Mindfulness: A Rasch Analysis of the Freiburg Mindfulness Inventory - Siobhan Lynch (Religions, 2011)
The objective of the study was to assess the psychometric properties of the Freiburg Mindfulness Inventory (FMI-14) using a Rasch model approach in a cross-sectional design. The scale was administered to N = 130 British patients with different psychosomatic conditions. The scale failed to show clear one-factoriality and item 13 did not fit the Rasch model. A two-factorial solution without item 13, however, appeared to fit well. The scale seemed to work equally well in different subgroups such as patients with or without mindfulness practice. However, some limitations of the validity of both the one-factorial and the two-factorial version of the scale were observed. Sizeable floor and ceiling effects limit the diagnostical use of the instrument. In summary, the study demonstrates that the two-factorial version of the FMI-13 shows acceptable approximation to Rasch requirements, but is in need of further improvement. The one-factorial solution did not fit well, and cannot be recommended for further use.